IQLIM O’ZGARISHLARINING HUDUDIY TAXLILI - Umirqulov Axrorbek Ilhom o’g’li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
At present, the temperature on the whole earth is increasing year by year. Global climate warming, drought, increase of infectious diseases, drastic reduction of flora and fauna, food crisis, and similar extreme situations are waiting for us in the near future. Due to global warming, our country, located inland and far from oceans and seas, has a number of negative and positive consequences. In this article, we have touched on a number of negative and positive consequences of global climate change affecting the Republic of Uzbekistan.